Origin recognition complex binding to a metazoan replication origin. - Bielinsky, A.K.; Blitzblau, H.; Beall, E.L.; Ezrokhi, M.; Smith, H.S.; Botchan, M.R.; Gerbi, S.A. (Current Biology, 2001)
The initiation of DNA replication in eukaryotic cells at the onset of S phase requires the origin recognition complex (ORC) [1]. This six-subunit complex, first isolated in Saccharomyces cerevisiae [2], is evolutionarily conserved [1]. ORC participates in the formation of the prereplicative complex [3], which is necessary to establish replication competence. The ORC-DNA interaction is well established for autonomously replicating sequence (ARS) elements in yeast in which the ARS consensus sequence [4] (ACS) constitutes part of the ORC binding site [2, 5]. Little is known about the ORC-DNA interaction in metazoa. For the Drosophila chorion locus, it has been suggested that ORC binding is dispersed [6]. We have analyzed the amplification origin (ori) II/9A of the fly, Sciara coprophila. We identified a distinct 80-base pair (bp) ORC binding site and mapped the replication start site located adjacent to it. The binding of ORC to this 80-bp core region is ATP dependent and is necessary to establish further interaction with an additional 65-bp of DNA. This is the first time that both the ORC binding site and the replication start site have been identified in a metazoan amplification origin. Thus, our findings extend the paradigm from yeast ARS1 to multicellular eukaryotes, implicating ORC as a determinant of the position of replication initiation.